Motivation, Creative Process and Characteristics of Abu Maestro's Acapella Works - Soraya, Elok (Universitas Negeri Surabaya, 2025)
This research aims to analyse Abu Maestro's existence as an a acapella music content creator by examining the background, creative process, and characteristics of his work. This research uses a qualitative method. The results show that his childhood experience and intrinsic drive influence Abu Maestro's motivation in creating music. His creative process began with his interest in seeing his uncle practice vocal groups, then he experienced a hiatus due to academic and organisational activities. This interest resurfaced when he became a vocal coach in Islamic spiritual extracurricular activities during high school, but again stopped because of his focus as a motivator. Inspiration from the group Neri Per Caso prompted him to produce his first video with the concept of one-man a acapella. The characteristics of his work include distinctive vocal timbre, imitation of instrument sounds, a wide range of tones, beatboxing techniques, improvised riffs and runs, complex vocal harmonies, and song selection that follows popular music trends. This research contributes to music studies, especially in the field of creativity and vocal-based digital music content production.